Heterotopic pancreas presenting with upper GIT bleeding - Hakim, HAN; Ali, M; Khan, AS; Alam, KZ; Rabbi, H; Islam, MA (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13251 J. Dhaka Med. Coll. 2012; 21(1): 120-123